Eligibility to Use the Fund's Facilities for Concessional Financing, 2020. (Policy Papers; Policy Paper ;, 2020)
This paper concludes that the existing framework remains broadly appropriate, but proposes methodological refinements to improve the assessment of market access, clarifies how serious short-term vulnerabilities are assessed, and proposes a modest extension of the transition period before graduation decisions become effective.